Inhibitory pompy protonowej a mikrobiom przewodu pokarmowego - Łoś-Rycharska, Ewa; Czerwionka-Szaflarska, Mieczysława (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Proton pump inhibitors are among the most widely used drugs. Until now they are considered as safe, but they also have side effects. Among them is the interference in the intestinal microbiome, which may result in gastrointestinal infections, including severe ones.